Evaluating critical criteria for green hospital buildings. Issue 1 (July 2020) - Huang, Hsiang-Hsun; Huang, Yu-Ying; Perng, Yeng-Horng
Abstract: Greening building is an increasingly important concern and a challenge in construction industry. The purpose of this paper is to evaluate the weights of criteria for green hospital buildings that provides decision-makers the priorities strategy in greening process. AHP was applied in this study to establish the hierarchy structure and evaluate the weight of criteria for green hospital buildings. The result indicated that sustainable site, energy saving, and water efficiency are the top three criteria. In the overall ranking, the top three significant sub-criteria are design of layout, greening of site, and energy saving for façade. The contribution of this study is to help decision-makers understand the relatively important of criteria to make decision for green hospital projects for sustainable development.